Mejores Prácticas de Manejo en el Area Agrícola de los Everglades: Pruebas de Suelos - Samira H. Daroub; Orlando A. Diaz; Timothy A. Lang; Viviana M. Nadal; Ming Chen (EDIS)
SL-225-Sp, a 6-page illustrated fact sheet by S.H. Daroub, O.A. Diaz, T.A. Lang, V.M. Nadal, and M. Chen, is the Spanish language version of SL-225, "Best Management Practices in the Everglades Agricultural Area: Soil Testing." It outlines the process of soil testing as an important tool for both fertilizer recommendations and as a BMP in this region. Includes references. Published by the UF Department of Soil and Water Sciences, May 2007.